Peningkatan aktivitas dan hasil belajar IPA melalui penerapan model Discovery Learning menggunakan media video pada siswa kelas V SD Negeri 1 Kaliori tahun pelajaran 2020/2021 - Eko Budi Raharjo (Jurnal Kualita Pendidikan, 2020)
The aim of this research is to find out how much student understanding of the various types of muscle learning material in humans increases, improves student learning outcomes and can foster a critical attitude towards performance results. The research was conducted through a cycled assessment process consisting of 4 stages (planning, implementing, observing, and reflecting) in 3 cycles of learning improvement. The data collection technique used in this CAR was a technical test, data collection conducted a test before and after the implementation of the discovery learning model using video media. The method used in this research is Classroom Action Research (PTK) with data collection techniques through observation, interviews, and documentation. The results of the research are quite good with an increase in the completeness of activities and learning outcomes for each cycle. The results of the preliminary study observation of 17 students who had met the learning completeness requirements were 5 students or 29.41% and 12 students who had not completed the study or 70.59% with an average value of 65.88 with 47% learning activeness, namely 8 students, in Cycle I the increase in student learning activities had reached 58%, namely 10 students, 10 students or 58% of completeness learning, and 7 students or 42% who had not completed the study with an average value of 75.28. Completeness of student learning outcomes in cycle II reached 14 students (82.35%), and students who had not completed were 3 students or 17.65% with an average score of 83.53 with 76.47% learning activeness, namely 13 students. Cycle III achieved 17 students (100%) completeness with an average score of 87.94. with learning, activity is also 100%. So it can be concluded that the application of the discovery learning model using video media can increase motivation and science learning outcomes in grade V SD Negeri 1 Kaliori in the 2020/2021 academic year.